Batman : the long Halloween - Loeb, Jeph; Kane, Bob (Batman., 2011)
A collection of Batman comics, originally published in thirteen monthly installments, following the efforts of the costumed crime fighter to save Gotham from a serial killer, a crime lord, and assorted gangsters and freaks.